The impact of the COVID-19 on the airline industry emerging from online comments - Piccinelli, Stefania (2021)
The aim of this research is to evaluate how the novel Coronavirus impact on the airline industry is reflected on the affected travelers’ concerns expressed in the comments they write online. In this study, a sample of 639 comments related to the airline industry, written on the website of the Italian National Consumer Union, has been assessed through an automated sentiment analysis. The achieved results showed that travelers’ attention was directed mainly towards compensations, cancellations, and COVID-19 and at the same time they had mixed and unpredictable feelings. This suggests that consumers may understood that airline companies are facing unsustainable cash-flow and revenue situations. Moreover, all the hypotheses, grounded on the existing literature were refuted. Accordingly, we argue that the actual context prevents assessments based on previous assumptions and studies related to the impact of COVID-19 need to be conducted anew.